Atmospheric methane concentrations on RV POLARSTERN cruise PS133/2, in 2022, from Punta Arenas to Cape Town - Ingeborg Bussmann; Sabine Kasten (PANGAEA, 2025)
Ambient methane concentrations were measured continuously by a LosGatos® greenhouse gas analyser (GGA) at a temporal resolution of 1 min. The GGA was calibrated regularly on board with gas sampling bags of standard gas and pure nitrogen (Airliquide). The inlet of the air was situated at the "crow extquotesingles nest" with an additional water trap. Wind data were obtained from the dship-system. The data set was filtered according to Thornton et al. 2016: Wind speed and direction were used to filter the data to avoid air contaminated by the ship. We include only data collected when the relative wind speed was >20.167emm0.167ems-1, and the relative wind direction was >280° and <80° relative to the ship extquotesingles bow. Any remaining observations with CO2 concentrations above 4500.167emppm were also removed.